pH-dependent structural dynamics of neuropeptide Y in aqueous solution - Hoa Thi Nguyen; Marc Spehr; Ana-Nicoleta Bondar; Paolo Carloni (PLoS ONE, 2026)
Neuropeptide Y regulates key molecular processes in the brain. Its interaction with the cell membrane, where it binds to specialized receptors with key physiological roles, likely depends on pH. Available structural ensembles of both porcine and human peptides, solved by nuclear magnetic resonance (NMR) at an acidic pH in aqueous solution, indicate an α -helical core with unstructured termini. However, the protonation states of the carboxylic and histidine residues of the peptide, as well as the interplay between these states and peptide conformational dynamics, remain unexplored. In this study, we performed constant pH simulations and graph-based analyses to investigate the dynamics and H-bond patterns of neuropeptide Y within a pH range of 3.0 to 7.0. We found that an α -helical core is present at all pH values, though its length can vary by 2–3 residues depending on the pH. The pK a of Asp16, part of the α -helix, and of Asp11 may shift by more than one pH unit. Based on these findings, we suggest that performing constant pH simulations may be required to accurately describe neuropeptide Y interactions with its cellular partners at the pH values of interest.